Evaluation of patients with suspected obstructive sleep apnea in a low-middle income country: Lagos experience - Oluwafemi Tunde Ojo; Adeola Olubunmi Ajibare; Akinola Olusola Dada; Rahmon Moronkola; Ayoola Odeyemi; Temitope Fapohunda; Ikechukwu Adolphus Aganweze; Tracy Udoka Ossai; Olufunke Olayinka Adeyeye; Ifeoluwa Owoeye (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2023)
Obstructive sleep apnea (OSA) is a common chronic disorder that decreases the quality of life of patients. It is an underdiagnosed medical condition in Nigeria. This study aimed to describe the clinical presentations and validate the sleep apnea screening questionnaires with a home sleep study for the diagnosis of patients with suspected OSA seen in Lagos. This was a descriptive cross sectional study carried out on adult patients with suspicion of OSA referred to the Respiratory Clinic of Lagos State University Teaching Hospital. A proforma was used to obtain information and also data from home polysomnography was obtained for each patient. We selected 22 patients. The commonest presentations include snoring (20 or 90.9%), daytime somnolence (16 or 72.7%) and choking while sleeping (12 or 54.5%). The commonest comorbidities were hypertension (16 or 72.7%) and obesity (6 or 27.3%). The STOP-Bang  score identified more patients with a high clinical probability for OSA than the Epworth score (20 and 12 patients respectively). Polysomnography showed evidence of sleep apnea in most suspected patients with severity ranging from mild, to moderate to severe disease (3 or 13.6%, 3 or 13.6%, and 10 or 45.5% respectively). The use of combined Epworth and STOP-Bang questionnaires combination is great tool in identifying patients with suspected cases of OSA based on clinical presentations that will eventually benefit in a resource-limited environment like Lagos. There should be increased awareness of the use of this readily available and cheap questionnaire among physicians in Lagos for ease of OSAS diagnosis for many patients.